Plato's Power - Araújo, Carolina, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
What do we mean when we say that something has power? Plato's dialogues are probably the first philosophical corpus to address this question. Powers are causes; they account for how events happen. They are properties that agents have, as well as dispositions in those who suffer the effects of an action. This explanation is the basis of Plato's metaphysics and moral philosophy. He proposed that things are the power they have to act or be acted upon; this is their nature. This book brings together a group of specialists to guide the reader through this fascinating theory.